2022
DOI: 10.1001/jama.2022.20982
|View full text |Cite
|
Sign up to set email alerts
|

Association of Medicare Advantage vs Traditional Medicare With 30-Day Mortality Among Patients With Acute Myocardial Infarction

Abstract: ImportanceMedicare Advantage health plans covered 37% of beneficiaries in 2018, and coverage increased to 48% in 2022. Whether Medicare Advantage plans provide similar care for patients presenting with specific clinical conditions is unknown.ObjectiveTo compare 30-day mortality and treatment for Medicare Advantage and traditional Medicare patients presenting with acute myocardial infarction (MI) from 2009 to 2018.Design, Setting, and ParticipantsRetrospective cohort study that included 557 309 participants wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…Elena Salmoirago-Blotcher, MD, PhD Ronald Cohen, PhD In Reply We thank Drs Salmoirago-Blotcher and Cohen for their interest in the MEDEX study, 1 which showed that mindfulness training and/or exercise did not improve cognitive function in older adults with subjective cognitive concerns. However, we disagree with their concern that the negative findings "can be explained by…methodological limitations."…”
Section: Mindfulness Training and Exercise And Cognitive Function In ...mentioning
confidence: 98%
See 3 more Smart Citations
“…Elena Salmoirago-Blotcher, MD, PhD Ronald Cohen, PhD In Reply We thank Drs Salmoirago-Blotcher and Cohen for their interest in the MEDEX study, 1 which showed that mindfulness training and/or exercise did not improve cognitive function in older adults with subjective cognitive concerns. However, we disagree with their concern that the negative findings "can be explained by…methodological limitations."…”
Section: Mindfulness Training and Exercise And Cognitive Function In ...mentioning
confidence: 98%
“…The Medicare Payment Advisory Commission (MedPAC) estimated that Medicare Advantage risk scores in 2021 were more than 10% higher than scores for similar beneficiaries in traditional Medicare . 1,2 To achieve these scores, Medicare Advantage plans rely on more intensive coding of diagnoses by their clinicians as well as chart audits and home visits to obtain additional diagnosis codes.…”
Section: Mindfulness Training and Exercise And Cognitive Function In ...mentioning
confidence: 99%
See 2 more Smart Citations
“…To the Editor A recent study compared outcomes of 30-day mortality following myocardial infarction in patients with Medicare Advantage vs traditional Medicare. However, greater coding intensity occurs in Medicare Advantage plans, which makes reliable interpretation of outcome data difficult when comparing Medicare Advantage plans with traditional Medicare.…”
mentioning
confidence: 99%